FENOMENA GAYA HIDUP BELANJA "PAKAIAN LELONG" IMPOR PADA MASYARAKAT KECAMATAN PEMANGKAT KABUPATEN SAMBAS - Harima, Harima; Buwono, Sri; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research was conducted on the Pemangkat District Community of Sambas Regency with the aim of this study to determine the lifestyle of buying imported lelong clothes in the Pemangkat Community of Sambas Regency in terms of activity, interest, and opinion aspects. This study uses a qualitative approach, with the type of phenomenological research. Informants in this study were determinedby using snowball sampling and purposive sampling techniques amounted to 10 people. The results of this study indicate that the people of Pemangkat District, Sambas Regency are more interested in buying imported lelong clothes to meet their needs in dressing. In the activity aspect, it can be seen the intensity of the community in shopping, the specific time of the community, the type of clothingpurchased, the costs spent, activities to meet the needs of clothing, and the habits carried out before buying importd auction clothes. Interest occurs in the choice of people who are more interested in buying auction clothes, when people are interested in seeing shops selling auction clothes, liking branded and quality clothes, and prioritizing the types of clothes to be purchased. The lifestyle of buying auction clothes in the opinion aspect occurs in people's views of themselves when they want to shop for auction clothes, the quality of clothing products sold, as well as cultural factors that influence people to participate in shopping for imported auction clothes.